A distinct hollow spindle-like CdIn2S4 photocatalyst for high-efficiency tetracycline removal. (June 2022) - Gao, L.; Chen, Z.; Zheng, H.; Hu, J.
Abstract: Due to the massive release of antibiotics into the environment, it is of great emergency to find an effective approach to deal with antibiotic-containing wastewater. Photocatalytic technology, benefiting from its low cost and high efficiency, is deemed to be an appealing strategy. Photocatalytic-induced production of reactive oxygen species (ROS) is a promising but challenging prospect in water purification and environmental remediation. Herein, we fabricated a spindle-like hollow CdIn2 S4 (HCIS) photocatalytic system for high-efficiency tetracycline removal. Targeting MIL-88A (Fe) as a template, the obtained CdIn2 S4 photocatalysts reserved intrinsic spindle-like morphology. Compared with Bulk CdIn2 S4 (BCIS), this unique hollow structure enhanced light absorption capacity and boosted carriers separation. As a result, the photodegradation efficiency reached over 94.5% within 40 min under visible light illumination. The degradation rate constant was four times higher than that of pristine CdIn2 S4 . We believe this work will endow some lights for the design of hollow catalysts in other environmental applications. Graphical abstract: Image 1 Highlights: A spindle-like hollow CdIn2 S4 was prepared via hydrothermal method for the first time. A Fe-based metal-organic framework MIL-88A was used as a template. Hollow structure improves light utilization and promotes carrier separation and transport. The reaction rate constant for TC degradation was four times higher than that of the pristine CdIn2 S4 .